Thea Stilton and the cherry blossom adventure - Stilton, Geronimo; Battan, Alessandro; OverDrive, Inc. (New York, NY : Scholastic, 2011)
The Thea sisters are off to Japan on a cultural exchange program. While they're busy exploring Kyoto and admiring the beautiful cherry blossoms, a valuable item is stolen from their friend Kumi's family. Will the five mice be able to catch the thief?
Interest age level: Ages 7-10.
Translation of: Il mistero della bambola nera.
Keywords: Stilton, Thea -- Juvenile fiction; Stilton, Geronimo -- Juvenile fiction; Mice -- Juvenile fiction; Sisters -- Juvenile fiction; Exchange of persons programs -- Juvenile fiction; Theft -- Juvenile fiction; Flowering cherries -- Juvenile fiction; Exchange of persons programs; Flowering cherries; Mice; Sisters; Stilton, Geronimo (Fictitious character); Stilton, Thea (Fictitious character); Theft; Electronic books; Fiction; Juvenile works